Me as a Building - Andreas Angelidakis (Footprint)
Andreas Angelidakis works between the various fields of curating, theory, architecture and the arts. In his position text the author reflects on the way he develops new narrative and design methods as part of a personal project of a challenging self-reflexive and psychological nature. States of being become inherently fluid as illustrated by the project Troll, which Angelidakis suggests is an autobiographical project, in which a building wants to leave the city to become a mountain: human bodies transition into nature into architecture, and back again. Describing his work and growing up in his hometown Athens Angelidakis discusses architecture and queer identities in terms of being ‘unauthorised’.